2008
DOI: 10.1007/s10964-008-9312-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining Temporal Associations Between School Connectedness and Early Adolescent Adjustment

Abstract: This study examined (a) the associations between school connectedness and early adolescent adjustment problems over a 1 year period and (b) the equivalence of these associations across gender. Five hundred middle school students (53.4% female), initially in the 6th and 7th grades, participated in the two-wave study. Results from two-group cross-lagged panel analyses were consistent across boys' and girls' data. After controlling for baseline levels of adjustment problems, school connectedness predicted lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 34 publications
14
75
1
2
Order By: Relevance
“…When young people receive empathy and attention in a consistent fashion, they feel valued. These experiences generate a sense of belonging which, in turn, leads to increased engagement and academic motivation (Loukas, Ripperger-Suhler, & Horton, 2009). In addition to theory, empirical research increasingly supports the necessity to develop effective learning environments that are sensitive to the needs of the participants.…”
Section: School Climate and Adolescent Risky Behaviorsmentioning
confidence: 99%
“…When young people receive empathy and attention in a consistent fashion, they feel valued. These experiences generate a sense of belonging which, in turn, leads to increased engagement and academic motivation (Loukas, Ripperger-Suhler, & Horton, 2009). In addition to theory, empirical research increasingly supports the necessity to develop effective learning environments that are sensitive to the needs of the participants.…”
Section: School Climate and Adolescent Risky Behaviorsmentioning
confidence: 99%
“…For example, Shocket and colleagues [40] found that early adolescents’ perception of school belongingness predicted future depressive symptoms in boys and girls; anxiety in girls; and conduct problems in boys. Other studies suggest bidirectional relationships between these constructs, which vary depending on the type of mental health domain being measured [41]. Loukas and colleagues [41] presented evidence of a bidirectional loop between school belongingness and conduct problems, but not depressive symptoms in 10–14 year old typically developing youth [41].…”
Section: Mental Health Problems In Adolescencementioning
confidence: 99%
“…Que la agresión se muestre predictiva de la depresión indica la importancia para el diagnóstico de lo que Cytryn y McKew (1972) etiquetaron como depresión enmascarada. Se trata de una depresión que aparece frecuentemente en la infancia y que enmascara lo que algunos autores han denominado equivalentes depresivos, entre los que destacan conductas problemá-ticas, tales como somatizaciones, delincuencia, agresividad e irritabilidad (Loukas, Ripperger-Suhler, & Horton, 2009;Mitchell, Varley, & McCauley, 1988).…”
Section: Discussionunclassified